2001
DOI: 10.1002/jez.1106
|View full text |Cite
|
Sign up to set email alerts
|

Steroid enzyme gene expressions during natural and androgen‐induced gonadal differentiation in the rainbow trout, Oncorhynchus mykiss

Abstract: In fish, according to Yamamoto's model, androgens would drive testis differentiation and estrogens ovarian differentiation. In order to study the implication of steroid enzymes in rainbow trout gonadal differentiation, we examined the expression of some steroid enzyme genes during natural differentiation (cholesterol side chain cleavage = P450scc, 17-hydroxylase/lyase = P450c17, 3beta-hydroxysteroid dehydrogenase = 3betaHSD) and androgen-induced differentiation (P450scc, P450c17, 3betaHSD, aromatase = P450aro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…The masculinizing effects of androgens are probably triggered by the suppression of estrogen synthesis through inhibition of aromatase gene expression. The inhibition of aromatase following androgen treatment in females has already been reported in rainbow trout (Govoroun et al 2001b). Here we have shown that an aromatase inhibitor can also induce a similar expression profile.…”
Section: Foxl2 Orthologs and Paralogs In Fishsupporting
confidence: 81%
See 2 more Smart Citations
“…The masculinizing effects of androgens are probably triggered by the suppression of estrogen synthesis through inhibition of aromatase gene expression. The inhibition of aromatase following androgen treatment in females has already been reported in rainbow trout (Govoroun et al 2001b). Here we have shown that an aromatase inhibitor can also induce a similar expression profile.…”
Section: Foxl2 Orthologs and Paralogs In Fishsupporting
confidence: 81%
“…Total RNA was isolated using TRIzol reagent (Invitrogen) as previously described (Govoroun et al 2001b). Total RNA concentration was determined with an Agilent 2100 Bioanalyzer and the RNA 6000 LabChip kit (Agilent Technologies, Colorado Springs, CO, USA) according to the manufacturer's instructions.…”
Section: Total Rna Extraction and Reverse Transcription (Rt)mentioning
confidence: 99%
See 1 more Smart Citation
“…This late steroidogenic potential is probably the reflection of a late differentiation and/or proliferation of the Leydig cell lineage, as we only detected very few positive cells for cyp17a1, cyp11a1, and cyp11b2.1 during this period of testicular differentiation. The previous studies carried out on trout were started at a late undifferentiated period (by 55 dpf) when steroid enzymes related to androgen synthesis displays a clear dimorphic expression in males (Liu et al, 2000;Govoroun et al, 2001). The present work confirms that steroid and androgen synthesis enzymes are up-regulated in male gonads but only after 45-55 dpf.…”
Section: Figmentioning
confidence: 99%
“…Despite the fact that androgenic treatments are able to induce a complete functionally phenotypic masculinisation of genetically all female populations (Liu et al, 2000;Devlin and Nagahama, 2002), the potential for androgen synthesis could not always be detected before testicular differentiation in teleost fish (Nakamura et al, 2003). For instance, in the Nile tilapia it has been suggested that androgen synthesis is absent during this process (Nakamura et al, 1998;Nakamura et al, 2003) whereas, in rainbow trout, some studies support the idea that endogenous androgens could drive testicular differentiation (Liu et al, 2000;Govoroun et al, 2001). However in rainbow trout these studies were carried out before the first sign of morphological go-nadal differentiation, and the expression of some genes was already sexually dimorphic at the earliest sampling point investigated, such as aromatase (cyp19a1) in females and 11␤-hydroxylase (cyp11b2.1) in males.…”
Section: Introductionmentioning
confidence: 99%